2019
DOI: 10.1521/aeap.2019.31.5.421
|View full text |Cite
|
Sign up to set email alerts
|

“The Drug Will Help Protect My Tomorrow”: Perceptions of Integrating PrEP into HIV Prevention Behaviors Among Female Sex Workers in Lilongwe, Malawi

Abstract: Female sex workers (FSW) are disproportionately at risk for HIV. Preexposure prophylaxis (PrEP) is an effective HIV prevention method, yet approaches for incorporating PrEP within prevention strategies used by FSW are lacking. Semistructured focus group discussions were conducted with 44 HIV-negative FSW in Lilongwe, Malawi to explore perceptions of PrEP: acceptability, integration within HIV prevention behaviors, and barriers to use. Acceptability of PrEP was high. Motivation to use PrEP was rooted in love fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Despite psychosocial and structural level factors presenting barriers to PrEP uptake [11][12][13][14][15][16], we found strong interest in this biomedical HIV prevention intervention among FSW in both study settings. HIV and sex-work related stigma along with realities of work conditions and environment are among the most pervasive factors creating barriers to oral PrEP among FSW, making LAI PrEP particularly appealing as it shows promise to overcome some of these challenges.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite psychosocial and structural level factors presenting barriers to PrEP uptake [11][12][13][14][15][16], we found strong interest in this biomedical HIV prevention intervention among FSW in both study settings. HIV and sex-work related stigma along with realities of work conditions and environment are among the most pervasive factors creating barriers to oral PrEP among FSW, making LAI PrEP particularly appealing as it shows promise to overcome some of these challenges.…”
Section: Discussionmentioning
confidence: 97%
“…Participants called for educating peers, partners, and clients about PrEP as a strategy for reducing stigma. Previous studies have also shown that FSW believe increased awareness of PrEP among the general public is necessary to minimize stigma and facilitate access and adherence to PrEP [12,20,25]. Specifically, educating communities about HIV treatment versus prevention has been identified by FSW as critical to PrEP roll out [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, respondents identifying as sex workers (regardless of gender) reported higher levels of anticipated, perceived and internalized PrEP‐related stigma, suggesting PrEP‐related stigma may be different among sex workers than others. While we did not measure sex work stigma directly, this relates to other literature describing intersecting PrEP and sex work stigmas [8, 11, 39]. Indeed, scholars have identified intersections between PrEP‐related stigma and other forms of stigma and discrimination (including racial discrimination, transphobia, sexual stigma and others) in other populations [7, 17, 40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…While there are studies examining barriers and facilitators to WESW’s access and use of health services related to HIV testing and counseling, and HIV treatment, there is limited research on the acceptability and appropriateness of comprehensive HIV prevention interventions that specifically target WESW, apart from studies that examine the acceptability of specific HIV risk reduction strategies, such as PrEP or condom use among this population [ 20 23 ]. Also, few studies reported on the feasibility and acceptability of interventions targeting WESW prior to implementation [ 24 , 25 ] or examined service provider perceptions of feasibility and acceptability of implementing evidence-based practices for preventing HIV/AIDS and STIs among WESW [ 26 ].…”
Section: Introductionmentioning
confidence: 99%